2021
DOI: 10.1021/acs.cgd.1c00406
|View full text |Cite
|
Sign up to set email alerts
|

A Zinc Coordination Polymer Sensor for Selective and Sensitive Detection of Doxycycline Based on Fluorescence Enhancement

Abstract: In this work, a novel coordination polymer HNU-55 has been synthesized by the reaction of Zn(II) ion with the organic ligand 3-pyridinesulfonic acid (PSA) under solvothermal condition, which can be used as a fluorescent sensor for the detection of doxycycline (DOX). The fluorescent performance is effective in a wide linear range from 0 to 30 μM of DOX with a low detection limit of 3.7 nM. Likewise, the fluorescent sensor presents good selectivity, anti-interference, and circularity. Additionally, the HNU-55 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 42 publications
(68 reference statements)
0
18
0
Order By: Relevance
“…The UV–Vis absorption spectra show that there was an obvious change of the absorption band upon the addition of l -His, which revealed that there may exist the interaction between L-His and JXUST-15 . 54 Besides, the shorter average fluorescence lifetime (τ av ) of JXUST-15 @ l -His (5.42 × 10 −3 ms) compared to JXUST-15 (6.07 × 10 −3 ms) also confirmed that there may exist the excited state interaction between l -His and JXUST-15 . 28 In addition, the excited electrons transferred from a high-lying π*-type LUMO to the CB of the complex, which could result in fluorescence enhancement.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The UV–Vis absorption spectra show that there was an obvious change of the absorption band upon the addition of l -His, which revealed that there may exist the interaction between L-His and JXUST-15 . 54 Besides, the shorter average fluorescence lifetime (τ av ) of JXUST-15 @ l -His (5.42 × 10 −3 ms) compared to JXUST-15 (6.07 × 10 −3 ms) also confirmed that there may exist the excited state interaction between l -His and JXUST-15 . 28 In addition, the excited electrons transferred from a high-lying π*-type LUMO to the CB of the complex, which could result in fluorescence enhancement.…”
Section: Resultsmentioning
confidence: 78%
“…S8a, ESI†), which confirmed the existence of the interaction between acac and JXUST-15 . 54 In addition, the average fluorescence lifetime ( τ av ) was measured to evaluate the excited-state behaviour of JXUST-15 after soaking in acac, which exhibited a biexponential decay, and calculated using the formula τ av = ( A 1 τ 1 2 + A 2 τ 2 2 )/( A 1 τ 1 + A 2 τ 2 ). The fluorescence lifetimes demonstrated that there may exist an excited state interaction between acac and JXUST-15 , 28 because the fluorescence lifetime ( τ av ) of JXUST-15 @acac (5.59 × 10 −3 ms) was shorter than that of JXUST-15 (6.07 × 10 −3 ms) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4e), indicating coordination between the Zn of HP-ZIF-8 and the C–O and CO groups of DOX. 69–71 As for N 1s fitting, the 398.46 eV peak belonged to imidazole linkers, while the 398.97 eV peak was assigned to the Zn–N bond (Fig. 4f).…”
Section: Resultsmentioning
confidence: 97%
“…As shown in the figure, HNU‐61 has no absorbance, and TCY has a maximum absorption wavelength at 367 nm. However, the maximum absorption wavelength of HNU‐61 and TCY mixture is 386 nm, which better proves the interaction between Zn 2+ and TCY when TCY is added, [ 17,18,32 ] and the fluorescence is sensitized by TCs.…”
Section: Resultsmentioning
confidence: 98%